SIMULATION OF SURFACE RUNOFF REDUCTION IN URBAN BUFFER AREA USING GREEN ROOF SYSTEM - Mubarak, Muhammad (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2018)
Steady developmental increase in urban and its buffer areas causes a decrease in rainwater catchment areas. Green roof system is emerging as a new form of technology that can improve the built environmental conditions. The purpose of this study was to simulate the application of green roof systems with cocopeat as planting media in reducing surface runoff water in urban buffer zones. Sub-watershed boundary analysis was carried out to determine the boundary of study area followed by land cover analysis using web-based software ?i-Tree Canopy? to obtain the area of roof cover within the study area. Rainfall analysis (2005-2014) was carried out to obtain the design flood discharge value at the study location. The simulation results show that the green roof system with 10 cm depth of cocopeat as planting medium is able to delay peak discharge in the study area to exceed the concentration time for all flood return periods. Green roof application simulation of 5% and 10% of the total roof cover area resulted in a reduction in peak discharge up to 3.12% and 6.24% respectively. This green roof system needs to be combined with rainwater harvesting systems to further reduce peak discharge in the study area.